(3TQM MeGSI CHj JeGes - (3jhSa Hf GdaVd Hf fXQ GdLRQjs; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3eGgGf (B((3HcQeGf(B) s)
(3ChdgG (B:s
(3bhe EPG GdTQ CHQi fGLOjg dge WGQhG Edjg RQGaGJ hhMOGfG s
(3BNQgG (B:s
(3dG JYdb HgeG HNOeIGdfSGA HMGd hbO ChQOgG CHh JeGe gGgfG Je cJGH GdMeGSI s
(3ecedI ai ChdgG Hbde eJCNQ SfI (B1183(3g`s
(3HChdgG agQS dCHhGH GdTYQs
(3hYdjgG JedjcGJ hbQGAGJ CbOegG SfI (B1204 s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs